Penyuluhan Tentang Perilaku Hidup Bersih dan Sehat (PHBS) dengan cuci Tangan di SMP Plus Al-Azhar Bekasi - Yusi Sofiyah (Compromise Journal Community Proffesional Service Journal, 2024)
Children are one of the individuals most at risk of being affected by unhealthy lifestyles. Adults must practice clean and healthy living behaviors continuously and correctly. Children will have a pattern of clean and healthy living behavior that will be practiced throughout their lives. In reality, there are still many children, especially early adolescents, have not been exposed to the importance of PHBS. This activity was carried out with the aim of increasing the knowledge of junior high school students regarding the prevention of infectious diseases. This activity was carried out through zoom media to male and female students of grade 7 of Al Azhar Bekasi Middle School. The results of the study showed that there was an increase in student knowledge before and after receiving counseling on PHBS hand washing.